Analisis Hambatan dan Tantangan: Implementasi Kurikulum Merdeka dalam Kehidupan Sehari-hari Guru - Soleha, Zachro; Mujahid, Kasori (Lembaga Yasin AlSys, 2024)
This research discusses the analysis of the obstacles and challenges faced by teachers in implementing the Independent Curriculum. The Merdeka Curriculum is an educational innovation that aims to increase students' creativity and intelligence. However, the implementation process in the field often faces various obstacles that affect the effectiveness of learning. This study uses a qualitative approach with in-depth interviews with a number of teachers who have implemented the Merdeka Curriculum. Research findings identified several key barriers, such as lack of resources, uneven understanding, and challenges in integrating technology in learning. An in-depth analysis of these obstacles provides a comprehensive picture of the complexity of implementing the Merdeka Curriculum at the teacher level. The implications of these findings can contribute to improved training strategies and support for teachers to overcome the challenges faced in implementing this educational approach.